Considerations on the regulation of AI systems in the financial sector by the AI Act - Mazzini, Gabriele; Bagni, Filippo (Frontiers in Artificial Intelligence, 2023)
The proposal for the Artificial Intelligence regulation in the EU (AI Act) is a horizontal legal instrument that aims to regulate, according to a tailored risk-based approach, the development and use of AI systems across a plurality of sectors, including the financial sector. In particular, AI systems intended to be used to evaluate the creditworthiness or establish the credit score of natural persons are classified as "high-risk AI systems". The proposal, tabled by the Commission in April 2021, is currently at the centre of intense interinstitutional negotiations between the two branches of the European legislature, the European Parliament and the Council. Without prejudice to the ongoing legislative deliberations, the paper aims to provide an overview of the main elements and choices made by the Commission in respect of the regulation of AI in the financial sector, as well as of the position taken in that regard by the European Parliament and Council.